Ethnobotanical use and conservation assessment of medicinal plants sold in markets of Burkina Faso - Ouedraogo, Lassané; Endl, Josef; Sombié, Pierre Alexandre Eric Djiffaby; Schaefer, Hanno; Kiendrebeogo, Martin (Ethnobotany Research and Applications, 2020)
Background: A comprehensive survey on the trade and use of medicinal plants in Burkina Faso was carried out with the aim of identifying the most relevant species and their conservation status. Methods: Interviews of 30 medicinal plant traders in six major cities was carried out and the data on medicinal plant species were recorded using a structured questionnaire. Results: A total of 104 medicinal plant species, belonging to 39 families and 81 genera were reported to treat various health problems. Most of the medicinal plant species found in the markets were used for gastrointestinal diseases (48%), e.g., Pteleopsis suberosa (Combretaceae) and Bauhinia rufescens (Fabaceae). The combination of fidelity level and preference ranking identified Gardenia sokotensis, Combretum micranthum and Maytensus senegalensis as particularly important species for treatment of malaria. Four species found in local markets are listed as vulnerable in the IUCN red list of threatened species (Afzelia africana, Vitellaria paradoxa, Khaya senegalensis and Tapinanthus globiferus). For many species that are traded in large quantities sufficient data for precise assessment of their conservation status do not yet exist. Some species such as Securidaca longipedunculata and Zanthoxylum zanthoxyloides are already rare in nature and sold at high price on the stalls. Conclusions: There is an urgent need to collect distribution data for the medicinal plant species of Burkina Faso and design conservation plans in order to preserve their natural populations. Keywords: Ethnobotanical survey; Medicinal plants; Conservation status; Traditional knowledge; Diseases; Burkina Faso